Treatment duration and dosage of valproic acid and subclinical hypothyroidism incidence in pediatric epilepsy patients - Carolina, Infra Yunita; Anidar, Anidar; Andid, Rusdi; Yusuf, Sulaiman; Darussalam, Dora; Sovira, Nora (Paediatrica Indonesiana, 2024)
Background Epilepsy is a central nervous system disorder characterized by abnormal electrical activity in the brain.1 Prolonged administration of valproic acid at therapeutic doses can disrupt thyroid function, leading to subclinical hypothyroidism. This condition is marked by elevated thyroid stimulating hormone (TSH) levels, with normal serum free T4 (FT4) levels.2 Objective To investigate for possible associations between valproic acid therapy duration and dosage with the incidence of subclinical hypothyroidism in pediatric epilepsy patients. Methods This analytical, cross-sectional study included children aged 4 months to 18 years treated at the Pediatric Clinic of RSUD Dr. Zainoel Abidin, Banda Aceh, from September to November 2023. Subjects diagnosed with epilepsy and treated with valproic acid for at least 3 months were included in this study and underwent FT4 and TSH examinations. Results Forty-four children met the study criteria. Subclinical hypothyroidism occurred in 5 (11.4%) subjects during valproic acid therapy. Chi-square analysis revealed no significant association between therapy duration ?1 year (OR 1.286; 95%CI 0.193 to 8.568; P=1.00) or therapy dose ?20-40 mg/kg/day (OR 3.429; 95%CI 0.351 to 33.518; P=0.37) with subclinical hypothyroidism incidence. Conclusion Neither the duration nor the dosage of valproic acid therapy were significantly associated with the incidence of subclinical hypothyroidism in children with epilepsy.